2006
DOI: 10.2224/sbp.2006.34.5.499
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Relationship Between Positive Affect and Both Problem- And Emotionfocused Coping Strategies

Abstract: The relationship between positive affect (PA), negative affect (NA) and reported use of problem-focused or emotion-focused coping strategies was investigated in a longitudinal study. Japanese undergraduates (200 men and 270 women) completed a version of the PANAS (Watson, Clark, & Tellegen, 1988) and the situational version of the General Coping Questionnaire (Sasaki & Yamasaki, 2004). These two measures were administered twice, five weeks apart (T1 and T2). The results showed some significant sex dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
3
20
1
1
Order By: Relevance
“…There were weak, but statistically significant, correlations between PA and NA (rs = .21 for men and .18 for women, ps < .01). Although these positive correlations are inconsistent with those in previous research showing either negative (e.g., Watson et al, 1988) or null correlations (e.g., Pettit et al, 2001), Yamasaki, Sakai, and Uchida (2005) suggested that this tendency may be characteristic of Japanese samples. As for the correlations between affect and the four subscales in GHQ, all of the correlations between NA and the four subscales were significantly positive, while the significant correlations between PA and the subscales were limited to the two subscales of Social Dysfunction and Severe Depression in both genders, all of which were negative.…”
Section: Resultscontrasting
confidence: 99%
“…There were weak, but statistically significant, correlations between PA and NA (rs = .21 for men and .18 for women, ps < .01). Although these positive correlations are inconsistent with those in previous research showing either negative (e.g., Watson et al, 1988) or null correlations (e.g., Pettit et al, 2001), Yamasaki, Sakai, and Uchida (2005) suggested that this tendency may be characteristic of Japanese samples. As for the correlations between affect and the four subscales in GHQ, all of the correlations between NA and the four subscales were significantly positive, while the significant correlations between PA and the subscales were limited to the two subscales of Social Dysfunction and Severe Depression in both genders, all of which were negative.…”
Section: Resultscontrasting
confidence: 99%
“…After five weeks, participants were invited back to complete a second survey (t2) that captured their current trust perceptions, satisfaction and behavioral intentions. Five weeks was considered in Yamasaki et al (2006) as being a good compromise for a time period for longitudinal study of behavior and personality. The measurements are discussed below.…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that coping is a key factor determining ones’ adjustment, which plays a mediating role in a stress process [14]. However, with respect to affect changes, previous findings have confirmed only the role of coping in PA changes [17]. Thus, it was hypothesized that problem-focused coping would mediate changes in affect balance and PA, whereas emotion- and avoidance-focused coping would mediate NA changes.…”
Section: Introductionmentioning
confidence: 99%